2014
DOI: 10.2478/achi-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of type of precursors on the sol-gel synthesis of the LaCoO3 nanoparticles

Abstract: Perovskite-type LaCoO3 was prepared by sol-gel method using nitrates / chlorides as precursors and citric acid as chelating agent. Chemical composition was obtained by means of EDX method. The structures of sintered samples were investigated by scanning electron microscopy (SEM), IR and XRD analysis. The results of X-ray diffraction indicated that the LaCoO3nanopowders obtained using nitrate as precursors had a rhombohedral perovskite-type crystal structure (S. G: R-3c), while that obtained using chloride as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Several compounds that have been tested as modifying agents are citric acid 44,45 , glycine nitrate 46 , and ammonium carbonate 47 . In general, it was reported that the use of modifier in sol-gel process resulted in better characteristics of solid products, compared to those of the products produced without modifier, such as more homogeneous surface, smaller particle size, and narrower particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds that have been tested as modifying agents are citric acid 44,45 , glycine nitrate 46 , and ammonium carbonate 47 . In general, it was reported that the use of modifier in sol-gel process resulted in better characteristics of solid products, compared to those of the products produced without modifier, such as more homogeneous surface, smaller particle size, and narrower particle size distribution.…”
Section: Introductionmentioning
confidence: 99%